Variabilidade espacial de Arsénio em solos da bacia hidrográfica do Rio Águeda (Portugal-Espanha). - Antunes, I.M.H.R. (2015)
Variabilidade espacial de Arsénio em solos da bacia hidrográfica do Rio Águeda (Portugal-Espanha)